Students’ Perception during Negotiation of Meaning in Unfocused and Focused Tasks - Intan Hamzah (English Learning Innovation (englie), 2023)
This current study aimed to determine the students’ perception of using unfocused and focused tasks. The design of the study was qualitative. The subjects of the study were 10 medical students of UPT Balai Bahasa Universitas Malahayati. The data were collected through speaking tests and questionnaires. The speaking test of speaking focused and unfocused was administrated. The students’ utterances will be recorded and described. The data will be analyzed in which types of negotiation of meaning are done by the speakers.The results of the research showed that the student's perception, open-ended interview method aimed at measuring perceptions of unfocused and focused tasks served as the research instrument. The results showed that the two tasks indicated that the unfocused task was enjoyable to most of the students, yet they failed to get input for the development of their language quality because during the negotiation of meaning they focused more on meaning. Moreover, the focused task was enjoyable for higher language proficiency to do. Hence, it could be inferred that the focused task was not suitable for lower language proficiency.